Mobile health applications: awareness, attitudes, and practices among medical students in Malaysia - Julian Valerie, John Jembai; Wong, Charlene Yi Lin; Nur Alia, Muhammad Amir Bakhtiar; Siti Nursuraya, Md Lazim; Ling, Hwei Sung; Kuan, Pei Xuan; Chua, Pin Fen (Springer Nature, 2022)
Background The popularity of mobile health (mHealth) applications (or apps) in the field of health and medical education is rapidly increasing, especially since the COVID-19 pandemic. We aimed to assess awareness, attitudes, practices, and factors associated with the mHealth app usage among medical students.